5‐HTTLPR moderates the association between interdependence and brain responses to mortality threats. Issue 12 (17th September 2017) - Luo, Siyang; Yu, Dian; Han, Shihui
Abstract: While behavioral research suggests an association between cultural worldview and decreased anxiety of death, the underlying neurobiological mechanisms remain unclear. Using functional MRI, we investigated whether and how the serotonin transporter promoter polymorphism (5‐HTTLPR), which has been associated with mental disorders such as anxiety and depression, moderates the associations between a cultural trait (i.e., interdependence) and self‐report of death anxiety/depression and between interdependence and brain responses to mortality threats. Long/long and short/short allele carriers of the 5‐HTTLPR were scanned using fMRI while they performed a one‐back task on death‐related, death‐unrelated negative, and neutral words. Participants' interdependence and death anxiety/depression were assessed using questionnaires after scanning. We found that participants who assessed themselves with greater interdependence reported lower death anxiety/depression and showed decreased neural response to death‐related words in emotion‐related brain regions including the anterior cingulate, putamen, and thalamus. However, these results were evident in long/long allele carriers of the 5‐HTTLPR but not in short/short allele carriers who even showed positive associations between interdependence and neural activities in the anterior cingulate, putamen and thalamus in response to death‐related words. Our findings suggest candidate mechanisms for explaining the complex relationship between genotype, cultural traits, and mental/neural responses to mortality threats. Hum Brain Mapp 38:6157–6171, 2017 . ©2017 Wiley Periodicals, Inc.